The Role Of Pre-Marital Education In Building Sakinah Family - Uliyah, Taqwatul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The family is the smallest social unit in the life of mankind and is also the main milestone in carrying out life activities. From the family comes an expression where there is a desire and action to form and create a happy family. The focus of this research is to determine the role of pre-marital education in building a sakinah family. The method used in this research is a literature study approach through literature sources and from various other literature sources. Then analyzed and presented the data findings objectively. The results show that in general it can be said that a sakinah family is built on love that prioritizes aspects of communication and deliberation as a form of democratic relationship patterns that become a means for the realization of dialogical communication. So that with this communication, calm, peace, and tranquility in the household are achieved. Thus, pre-marital education is needed to provide insight into knowledge, understanding, skills and awareness to every prospective husband and wife who want to carry out marriage in order to create a prosperous family so as to give birth to a quality generation.